Troponin Serum Level in Ischemic Stroke Patients and its Prognostic Value - Farhad Iranmanesh; Akbar Hamzei-Moghadam; Mahbobeh Dehghan (Journal of Kerman University of Medical Sciences, 2019)
Background: Some recent studies have shown that troponin may have a Prognostic value in patients with ischemic stroke. This study seeks to to evaluate the prognostic value of troponin on 3 months mortality and recurrence in patients with ischemic stroke. Method: In this study 63 patients with ischemic stroke were evaluated. Embolic and lacunar stroke were excluded from the study. In the first 24 hours, serum troponin levels were measured. Patients were evaluated for a three-month period in terms of death and recurrence of stroke, and the results were analyzed using independent t-test and logestic regression. Results: In this study, 32 (50.8%) were male and the rest were female. Of the 63 patients studied, 8 (12.7%) had an abnormal troponin level. The mean serum level of troponin in patients who had died was 75.52 and patients who did not die was 38.2. This difference was statistically significant (p = 0.013). However, in the regression analysis, this result was not significant. Age (P=0.04) and NIHSS (P = 0.001) had a meaningful relationship with mortality. Of the 53 patients who were discharged, 5 (9.4%) had recurrence after 3 months. The mean serum level of troponin in patients with recurrence was 43.36 ±55.23 and mean serum troponin level in patients who did not relapse was 40.52 ±93.20. This difference was statistically significant (p = 0.54) Conclusion: Troponin has no prognostic value on three months mortality and recurrence rate in ischemic stroke patients.